2021
DOI: 10.1016/j.annonc.2021.05.353
|View full text |Cite|
|
Sign up to set email alerts
|

Ribociclib plus fulvestrant for postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer in the phase III randomized MONALEESA-3 trial: updated overall survival

Abstract: Background: Ribociclib plus fulvestrant demonstrated significant progression-free survival (PFS) and overall survival (OS) benefits in patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative (HRþ/HER2À) advanced breast cancer (ABC). Here we present a new landmark in survival follow-up for a phase III cyclin-dependent kinases 4 and 6 inhibitor clinical trial in patients with ABC (median, 56.3 months). Patients and methods: This phase III, randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
0
24

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(190 citation statements)
references
References 15 publications
5
161
0
24
Order By: Relevance
“…Patients remained on either treatment for one year. The overall survival (OS) for the group treated with ribociclib/fulvestrant was 51.8 months, compared to 39.7 months for the fulvestrant-only group [30]. These data suggested that ribociclib and fulvestrant could help to extend survival in both men and women with HR+ breast cancer.…”
Section: Ribociclibmentioning
confidence: 93%
“…Patients remained on either treatment for one year. The overall survival (OS) for the group treated with ribociclib/fulvestrant was 51.8 months, compared to 39.7 months for the fulvestrant-only group [30]. These data suggested that ribociclib and fulvestrant could help to extend survival in both men and women with HR+ breast cancer.…”
Section: Ribociclibmentioning
confidence: 93%
“…In metastatic disease, the CDK4/6 inhibitors associated with endocrine therapy radically changed clinical practice due to a remarkable improvement in terms of PFS compared to hormone therapy alone of 9-13 months in first line [9,10,15,16,24,25], of 8-11 months in both first second line [26][27][28][29]), and of 5-7 months in second line [11][12][13]22,23]. Those results have never been seen before and so this class of drugs entered quickly into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tucatinib showed a significant advantage of 4.5 months [40], atezolizumab demonstrated a non-statistically improvement of 3.7 months in the ITT population and an interesting clinical advantage of 9.5 months in PD-L1-positive patients [34,35], and talazoparib did not demonstrate a statistically significant benefit in OS [32,33]. The trials with an available OS update were those that evaluated CDK4/6 inhibitors in both the first and second line and second line, showing an improvement of 11-12 and 7-9 months, respectively [11][12][13]22,23,[26][27][28][29]. The other trials were SOLAR-1, in which alpelisib showed a non-statistically significant benefit in OS (8 months) [37,38], and the trials with PARP-inhibitors, where an advantage in OS was not demonstrated [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, in both the study program trials, namely the MONARCH-3 for abemaciclib and PALOMA-2 for palbociclib, any data on OS have not been reported yet and further results are expected. For ribociclib, however, a total of three trials have reported data on OS and show a consistent significant benefit that is independent from its use in the first or second treatment line, pre- or postmenopausal women, or with an AI or fulvestrant as ET partner [ 78 , 79 , 80 ]. In the MONALEESA-2 study, postmenopausal patients under first-line ribociclib and letrozole achieved a median OS of 63.9 months, the longest OS data reported for aBC to date [ 78 ].…”
Section: Modern Approaches In Advanced Breast Cancermentioning
confidence: 99%